The C Proteins of Human Parainfluenza Virus Type 1 Block IFN Signaling by Binding and Retaining Stat1 in Perinuclear Aggregates at the Late Endosome - Schomacker, Henrick (Public Library of Science, 2012)
Interferons (IFNs) play a crucial role in the antiviral immune response. Whereas the C proteins of wild-type human parainfluenza virus type 1 (WT HPIV1) inhibit both IFN-β induction and signaling, a HPIV1 mutant encoding a single amino acid substitution (F170S) in the C proteins is unable to block either host response. Here, signaling downstream of the type 1 IFN receptor was examined in Vero cells to define at what stage WT HPIV1 can block, and F170S HPIV1 fails to block, IFN signaling. WT HPIV1 inhibited phosphorylation of both Stat1 and Stat2, and this inhibition was only slightly reduced for F170S HPIV1. Degradation of Stat1 or Stat2 was not observed. The HPIV1 C proteins were found to accumulate in the perinuclear space, often forming large granules, and co-localized with Stat1 and the cation-independent mannose 6-phosphate receptor (M6PR) that is a marker for late endosomes. Upon stimulation with IFN-β, both the WT and F170S C proteins remained in the perinuclear space, but only the WT C proteins prevented Stat1 translocation to the nucleus. In addition, WT HPIV1 C proteins, but not F170S C proteins, co-immunoprecipitated both phosphorylated and unphosphorylated Stat1. Our findings suggest that the WT HPIV1 C proteins form a stable complex with Stat1 in perinuclear granules that co-localize with M6PR, and that this direct interaction between the WT HPIV1 C proteins and Stat1 is the basis for the ability of HPIV1 to inhibit IFN signaling. The F170S mutation in HPIV1 C did not prevent perinuclear co-localization with Stat1, but apparently weakened this interaction such that, upon IFN stimulation, Stat1 was translocated to the nucleus to induce an antiviral response.